Selective enrichment on a wide polysaccharide spectrum allowed isolation of novel metabolic and taxonomic groups of haloarchaea from hypersaline lakes - Sorokin, Dimitry Y.; Elcheninov, Alexander G.; Khijniak, Tatiana V.; Kolganova, Tatiana V.; Kublanov, Ilya V. (Frontiers in Microbiology, 2022)
Extremely halophilic archaea (haloarchaea) of the class Halobacteria is a dominant group of aerobic heterotrophic prokaryotic communities in salt-saturated habitats, such as salt lakes and solar salterns. Most of the pure cultures of haloarchaea were enriched, isolated and cultivated on rich soluble substrates such as amino acids, peptides or simple sugars. So far, the evidences on the capability of haloarchaea to use different polysaccharides as growth substrates remained scarce. However, it is becoming increasingly obvious that these archaea can also actively participate in mineralization of complex biopolymers, in particular cellulose and chitin - two dominant biomass polysaсcharides on the planet. Here we used an array of commercially available homo- and heteropolysaccharides to enrich hydrolytic haloarchaea from hypersaline salt lakes with neutral pH and from alkaline soda lakes. This resulted in isolation of a range of halo- and natrono-archaea, respectively, belonging to already described taxa as well as several new genus-level lineages. In some cases, the isolates enriched with different polysaccharides happened to be closely related, thus representing generalistic ecotype, while the others were narrow specialists. In general, soda lakes yielded a broader range of polysaccharide-utilizing specialists in comparison to neutral salt lakes. The results demonstrated a significant diversity of halo(natrono)archaea with a previously unrecognized potential for utilization of a broad range of natural polysaccharides in hypersaline habitats.